Determining the motivational factors for participation in team sports in Nanyang Technological University Students - Chang, Han Yun (2019)
The Singapore government has been constantly encouraging people to participate in sports and physical activities to stay healthy. Every year, numerous sporting events are held at various locations to encourage people to attend. However, motivation also plays an important role in team sport participation (Perlman Dana, 2014). This study seeks to determine and understand the motivating factors that drive the interest of students studying in Nanyang Technological University (NTU) to participate in team sports. A survey questionnaire was adopted from Sport Motivation Scale and Physical Activity and Leisure Motivation Scale. Self-administered questionnaire was used to collect data from NTU students who previously or are currently participating in team sport. 140 responses were recorded, consisting of 48 females and 136 males, aged 20 to 26. Team sports require students to interact and communicate with each other, hence it was hypothesized that friendship and teamwork are the main motivating factors for NTU students to participate in team sport, and that team sport promotes values such as friendship and teamwork. Microsoft Excel was used to evaluate and analyse the results to find the mean, median and mode of each motive to determine which motivation factor has the highest rating. Results showed that students in NTU were more intrinsically motivated (M=5.43) to participated in team sport than extrinsically motivated (M=4.27), with satisfaction gained being the highest means of motivation. These results will aid teachers, coaches and sports managers to conduct more events and campaigns to increase students’ opportunity to engage in sporting events.